Genocide and Mass Violence in Asia An Introductory Reader - Jacob, Frank (Genocide and Mass Violence in the Age of Extremes, 2019)
In Asia the "Age of Extremes" witnessed many forms of mass violence and genocide, related to the rise and fall of the Japanese Empire, the proxy wars of the Cold War, and the anti-colonial nation building processes that often led to new conflicts and civil wars. The present volume is considered an introductory reader that deals with different forms of mass violence and genocide in Asia, discusses the perspectives of victims and perpetrators alike.